Cell-cycle regulation in green algae dividing by multiple fission - Bišová, Kateřina; Zachleder, Vilém (Journal of Experimental Botany, 2014)
Green algae dividing by multiple fission comprise unrelated genera but are connected by one common feature: under optimal growth conditions, they can divide into more than two daughter cells. The number of daughter cells, also known as the division number, is relatively stable for most species and usually ranges from 4 to 16. The number of daughter cells is dictated by growth rate and is modulated by light and temperature. Green algae dividing by multiple fission can thus be used to study coordination of growth and progression of the cell cycle. Algal cultures can be synchronized naturally by alternating light/dark periods so that growth occurs in the light and DNA replication(s) and nuclear and cellular division(s) occur in the dark; synchrony in such cultures is almost 100% and can be maintained indefinitely. Moreover, the pattern of cell-cycle progression can be easily altered by differing growth conditions, allowing for detailed studies of coordination between individual cell-cycle events. Since the 1950s, green algae dividing by multiple fission have been studied as a unique model for cell-cycle regulation. Future sequencing of algal genomes will provide additional, high precision tools for physiological, taxonomic, structural, and molecular studies in these organisms.
Keywords: Cell Cycle; replikace DNA; Chlorophyta; světlo; Temperature; DNA Replication; teplota; buněčný cyklus; Light